Review on Emotion Recognition Based on Electroencephalography - Liu, Haoran; Zhang, Ying; Li, Yujun; Kong, Xiangyi (Frontiers in Computational Neuroscience, 2021)
Emotions are closely related to human behavior, family and society. Since changes in emotions can cause differences in electroencephalography (EEG) signals, EEG signals can show different emotion states and are not easy to disguise. EEG-based emotion recognition has been widely used in human-computer interaction, medical diagnosis, military and other fields. In this paper, we describe the common steps of emotion recognition algorithm based on EEG from data acquisition, preprocessing, feature extraction, feature selection to classifier. Then, we review the existing EEG-based emotional recognition methods, as well as assess their classification effect. This paper will help researchers quickly understand the basic theory of emotion recognition and provide references for the future development of EEG.